HUBUNGAN SIKLUS MENSTRUASI DENGAN GANGGUAN TIDUR PADA MAHASISWI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS AIRLANGGA ANGKATAN 2019 - Dhawam Decandra Putra; Bambang Purwanto; Jimmy Yanuar Annas (Jurnal Insan Farmasi Indonesia, 2023)
Factors that affect the menstrual cycle are hormones, enzymes, vascularization, prostaglandins, psychological factors, chronic disease, malnutrition, physical activity, and drugs. The prevalenceof menstrual cycle abnormalities in Indonesian adolescents is quite high, around 31.6%. Normal sleep disorders in women have risks to health, namely in mood disorders and cognitive function. This study aims to analyze the relationship between menstrual cycle length and sleep disturbances in female medical students. This research is an observational analytic research with cross sectional design. This research was conducted at the Faculty of Medicine, Airlangga University from September 2021 to November 2022. The subjects of this study were 60 female medical students from the Faculty of Medicine, Airlangga University, class of 2019. The independent variable in this study was the menstrual cycle, while the dependent variable in this study was sleep disturbances. Data analysis used in this study was bivariate analysis using fisher's exact test to test the menstrual cycle and sleep disturbances. The conclusion in this study is that there is no relationship between menstrual cycle length and sleep disturbances in female medical students at the Faculty of Medicine, Airlangga University class of 2019 with a value of (p> 0.05)